Reverse-sequence endoscopic nipple-sparing mastectomy with immediate implant-based breast reconstruction: an improvement of conventional minimal access breast surgery - Chung, Kawun; Xie, Yanyan; Liang, Faqing; Qiu, Mengxue; Yang, Huanzuo; Zhang, Qing; Dai, Hui; Du, Zhenggui (Frontiers in Oncology, 2024)
Background: Our center proposes a new technique that effectively provides space to broaden the surgical field of view and overcomes the limitations of endoscopy-assisted nipple-sparing mastectomy (E-NSM) by changing the dissection sequence and combining it with air inflation. The purpose of this study was to compare the clinical outcomes of the new technique designated "reverse-sequence endoscopic nipple-sparing mastectomy (R-E-NSM) with subpectoral breast reconstruction (SBR) " and the conventional E-NSM (C-E-NSM) with SBR.Method: All patients undergoing E-NSM with SBR at our breast center between April 2017 and December 2022 were included in this study. The cohort was divided into the C-E-NSM group and the R-E-NSM group. The operation time, anesthesia time, medical cost, complications, cosmetic outcomes, and oncological safety were compared.Results: Twenty-six and seventy-nine consecutive patients were included in the C-E-NSM and R-E-NSM groups, with average ages of 36.9±7.0 years and 39.7±8.4 years (P=0.128). Patients in the R-E-NSM group had significantly shorter operation time (204.6±59.2 vs. 318.9±75.5 minutes, p<0.001) and anesthesia time (279.4±83.9 vs. 408.9±87.4 minutes, p<0.001) and decreased medical costs [5063.4 (4439.6-6532.3) vs. 6404.2 (5152.5-7981.5), USD, p=0.001] and increase SCAR-Q scores (77.2±17.1 vs. 68.8±8.7, P=0.002) compared to the C-E-NSM group. Although trends increased in both the excellent rate of Ueda scores (53.8% vs. 42.3%, P = 0.144), excellent rate of Harris scores (44.0% vs. 63.1%, P=0.102), and decreased surgical complications (7.6% vs. 19.2%, P = 0.135) were observed in the R-E-NSM group, the differences were not significant. There were no significant differences in oncological outcomes between the two groups.R-E-NSM improves cosmetic outcomes and efficiency of C-E-NSM, reduces medical costs, and has a trend of lower surgical complications while maintaining the safety of oncology. It is a safe and feasible option for oncological procedures that deserves to be promoted and widely adopted in practice.